Solidarity in Social Work - Čepėnaitė, Angelė; Laiconienė, Rasa (Socialinė teorija, empirija, politika ir praktika, 2001)
The participants of discussion shared they opinions about the possible social services provision policies. The criteria for the evaluation of the policies were the efficiency, humanistic solidarity, justice, freedom and the correspondence with the requirements of globalisation and humanity development.